Alcohol use and alcohol‐related consequences based on gender and sexual orientation among college students. Issue 3 (6th April 2022) - Schipani‐McLaughlin, Anne Marie; Nielsen, Karen E.; Mosley, Elizabeth A.; Leone, Ruschelle M.; Oesterle, Daniel W.; Orchowski, Lindsay M.; Davis, Kelly C.; Gilmore, Amanda K.
Abstract: Background and Objectives: Research has not yet investigated how the association between alcohol and alcohol‐related consequences differs across cisgender heterosexual women (CHW), cisgender heterosexual men (CHM), and sexual and gender minority (SGM) college students. Methods: Participants were N = 754 college students (34.5% CHW [ n = 260]; 34.5% CHM [ n = 260]; 31.0% SGM [ n = 234]) between the ages 18 and 25 who completed a survey on sexual orientation, gender identity, alcohol use (i.e., average drinks per week), and alcohol‐related consequences. Results: Among individuals who reported alcohol use, CHM reported significantly more drinks per week compared to CHW and SGM. The logistic model of a zero‐inflated negative binomial regression indicated that excess zeros in the alcohol‐related consequences were more likely among (1) nondrinkers and (2) SGM compared to CHM. The count portion of the model indicated that, among drinkers, there was a positive association between drinks per week and alcohol‐related consequences. Estimated alcohol‐related consequences per drink were 1.90% higher among CHW than CHM and 2.76% higher among SGM than CHM. Exploratory analyses did not find significant differences in outcomes between cisgender female and male sexual minority students. Discussion and Conclusion: Findings suggest that although CHW and SGM students consume less alcohol than CHM, these students experience more alcohol‐related consequences per drink. Scientific Significance: This study advances the field's knowledge of alcohol use patterns and consequences among SGM college students. There is a need for alcohol education programming that is tailored to the unique experiences, identities, and minority stressors of SGM college students.